(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
This paper reports findings from the pilot study on Factors Affecting Library and Media Teachers (LMTs) Performance Improvement. Thirty-eight respondents involved were from the Teachers’ Activities Centre (TAC) of Kapar and TelokGadong Zone, Klang. Selangor. Respondents answered all the 151 questions on the Factors Affecting LMTs Performance Improvement (Skills and Knowledge), with motivation as the moderating factors (Commitment, Self-Efficacy, Reward, Task Complexity, Feedback) and LMTs’ Perception on two SRCM Courses (Basic and Intermediate) and also LMTs Performance Improvement. The 151 questions included 7 questions on profiles background. The overall Cronbach Alpha reliability on the items is 0.995, indicating that the measurement reflected high reliability. This study is specifically on research about factors (skills, knowledge, LMTs’ perception through Basic (35H) and Intermediate (45H) SRCM Courses), motivation as the moderator factors to improve LMTs’ performance. A central aim of this research is to explicate the effect’s relationships that exist among factors, and LMTs’ performance improvement.